PENERAPAN ALQURAN MORNING SERTA DAMPAK TERHADAP HAFALAN ANAK ANAK DI SDIT AL-BIRRU - Finta Fajar Fadillah; Yassir Hayati; Asmarika (Miftahul Ulum, 2024)
This research aims to improve students' ability to facilitate memorization of letters in the Koran through the implementation of the Al-Qur’an morning program at SDIT Al-Birru. The main problem is that SDIT Al-Birru students have difficulty memorizing, for this reason a program is needed to improve student memorization. This type of research is field research. Meanwhile, this research approach is descriptive qualitative, where in its implementation it analyzes the data and describes it. It is hoped that this research can improve the memorization of letters starting from short surahs up to juz 28, 29 and 30 for students at SDIT Al-Birru. The results of this research are to be able to find out the implementation of the Al-Qur’an morning program at SDIT Al-Birru and to find out the inhibiting and supporting factors for implementing the Al-Qur’an morning program at SDIT Al-Birru.